Efficacy of supplemental Occlu-pad therapy with partial occlusion in children with refractive anisometropic amblyopia - JitendraJethani; AnishaKamat; KalpitShah; HansaThakkar; SumedhaSharma (Indian Journal of Ophthalmology, 2022)
Purpose:To study the efficacy of supplemental occlu-pad therapy with partial occlusion in children with refractive anisometropic amblyopia. Methods: Thirty-one children who did not improve after partial occlusion of 6 h for 6 months were supplemented with the use of occlu-pad for 1 h per day and three such sessions in a week. Results: The mean age was 6.8+/-1.4 years (range 5–9 years). A significant improvement of 3.2+/-1.3 lines in visual acuity was noticed at the end of 3 months of starting this supplemental therapy in children. Out of 31 children, 26 children improved at least 2 lines or more at the end of 3 months. All children (n = 9) having anisohyperopic amblyopia improved at the end of 3 months. Conclusion: Occlu-pad is useful in supplementing occlusion therapy in cases of refractive amblyopia and is more effective in anisohyperopic amblyopia.